Encyclopedia of global environmental governance and politics - Pattberg, Philipp H.; Zelli, Fariborz; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2015)
The Encyclopedia of Global Environmental Governance and Politics surveys the broad range of environmental and sustainability challenges in the emerging Anthropocene and scrutinizes available concepts, methodological tools, theories and approaches, as well as overlaps with adjunct fields of study. This comprehensive reference work, written by some of the most eminent academics in the field, contains 68 entries on numerous aspects across 7 thematic areas, including concepts and definitions; theories and methods; actors; institutions; issue-areas; cross-cutting questions; and overlaps with non-environmental fields. With this broad approach, the volume seeks to provide a pluralistic knowledge base of the research and practice of global environmental governance and politics in times of increased complexity and contestation. Providing its readers with a unique point of reference, as well as stimulus for further research, this Encyclopedia is an indispensable tool for anyone interested in the politics of the environment, particularly students, teachers and researchers.
pt. 1. Concepts and definitions -- pt. 2. Theories and methods -- pt. 3. Actors -- pt. 4. Institutions -- pt. 5. Issue areas -- pt. 6. Cross-cutting questions and emerging topics -- pt. 7. Borders and interlinkages.
Includes index.
Keywords: Environmental policy -- Encyclopedias; Environmental protection -- Encyclopedias; Electronic books